Towards seamless source mobility in SSM: design and evaluation of the Tree Morphing protocol. (11th March 2009) - Christ, Olaf; Schmidt, Thomas C.; Wahlisch, Matthias
Multimedia networking in the near future is expected to be dominated by group applications such as IPTV. Driven by new services, multicast at the network layer started to disseminate. Currently infotainment is expanding into the mobile world, but a standard design of mobile multicast is still awaited. In this paper, we design and discuss the Tree Morphing (TM) protocol that adaptively manages trees to support seamless handovers for Source Specific Multicast (SSM) sources. Based on a full simulator implementation, we extensively explore its performance. By employing artificial networks, as well as real-world topologies, we analyse the handover behaviour conceptually and in realistic scenarios.